THE PERFORMANCE OF NEURAL MACHINE TRANSLATION IN THE INDONESIAN TRANSLATION OF THREE FUNDAMENTAL CATHOLIC PRAYERS - Harris Hermasnyah Setiajid; Marchelline Berliandika Saksono; Alma Anindita; Diksita Galuh Nirwinastu (Universitas Bandar Lampung, 2022)
Literary translation is one of the greatest obstacles to neural machine translation development (NMT). NMT precision is susceptible to common issues in literary texts, such as lexical ambiguity, complex syntax, and structural grammatical constructions. This study investigates the literary translation of three Catholic prayers: